1991
DOI: 10.1111/j.1432-1033.1991.tb16279.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the cDNA clone which encodes the 58‐kDa protein containing the amino acid sequence of rat liver non‐specific lipid‐transfer protein (sterol‐carrier protein 2)

Abstract: The relationship between the rat liver non-specific lipid-transfer protein (nsLTP) and the 58-kDa protein crossreactive with anti-nsLTP antibodies, was investigated by cDNA analysis. A 1945-bp cDNA clone was isolated which encodes a 58.7-kDa protein. This protein is identical to the 58-kDa immunoreactive protein determined by N-terminal sequence analysis of the purified 58-kDa protein. It consists of 546 amino acid residues, of which the 123 C-terminal residues are identical to the sequence of nsLTP. The N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…Molecular sieving experiments indicated that the enzyme may be present in the cell as a mixture of three dimeric isoforms consisting of homo-and heterodimeric combinations of the 58-and 46-kDa subunits. 4 The 58-kDa polypeptide has been purified from rat liver also by others but under denaturing conditions (16). The recombinant 58-kDa protein expressed in Escherichia coli possessed thiolase activity with straight chain 3-oxoacyl-CoAs (18).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Molecular sieving experiments indicated that the enzyme may be present in the cell as a mixture of three dimeric isoforms consisting of homo-and heterodimeric combinations of the 58-and 46-kDa subunits. 4 The 58-kDa polypeptide has been purified from rat liver also by others but under denaturing conditions (16). The recombinant 58-kDa protein expressed in Escherichia coli possessed thiolase activity with straight chain 3-oxoacyl-CoAs (18).…”
Section: Resultsmentioning
confidence: 98%
“…Molecular cloning of the protein revealed that it consists of an N-terminal 404 amino acid domain that shows homology with a number of thiolases and a C-terminal 143 amino acid domain that is identical to the N-terminal presequence (20 amino acids) and mature sequence (123 amino acids) of SCP-2 (16). The 58-kDa protein, which was called SCP-X, and SCP-2 are transcribed from a single gene that contains two independent promoters (17).…”
mentioning
confidence: 99%
“…Met-Giy-Phe-Pro-GiuS-Aia-AiaSer-Ser-Phe ~°-Arg-Thr-His-Gln-lle~S-Ser-Ala-AlaPro-Thr ~°. Based on cDNA analysis, it was found that the complete amino acid sequence of pre-nsL-TP ( kDa) is present at tile C-terminal end era 58-kDa protein [23,36,37]. However, pre-nsL-TP and the 58-kDa protein are synthesized from separate mRNA's.…”
Section: Discussionmentioning
confidence: 99%
“…2,2, Clotting of the eDNA sequence encoding rat fiver pre.nsL-TP in pET3d A eDNA clone (1851 bp) encoding a 58-kDa protein that contains the complete pre-nsL-TP sequence [23] (see discussion) was used in a pol~,merase chain reaction (PCR) [30] experiment to give a 505-bp DNA fragment encoding pre-nsL-TP, Two oliBonucleotid¢~ were synthesized and used in the PCR to create the appropriate restriction sites in this cDNA. With oligonucleotide 1, 5'.ACC,CTC.TAC,ACC,-ATG.GGT.T'I'r,CCC,GAA.Y, an Ncol site was created around the startcodon, and with oligonuelcotide 2, 5'.CGT,GGA,TTT.CTA.-CGG.ATC.CAC.ACA.TCT,C-3', a BamHl site was made 43--48 bp downstream or the stopcodon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation